Carotid Stenosis Leading to Acute Ischemic Stroke: The Sex-Age Aspect of Surgical Treatment - Alexander, Gavrilenko; Sebastian, Sanchez; Alexander, Abramyan; Andrey, Kuklin; Vladimir, Kramnik (International Journal of Psychosocial Rehabilitation, 2020)
Background: The prevalence of atherosclerotic disease of the cardiovascular system among both women and men of various age groups leading to serious ischemic stroke attracts a lot of negative changes in the working capacity of population. The tactics of surgical treatment of the carotid stenosis and acute ischemic stroke needs the further development. Methods: This retrospective study included 90 patients at Petrovsky National Research Center of Surgery. The study period was from 2000 to 2019. Collected data included results of duplex scanning and magnetic resonance imagining (MRI) of the brachycephalic arteries, MRI and computer tomography of the brain, angiography. To analyze obtained data, methods of descriptive statistics and correlation were used. Results: 45.56% of patients that were included into our study were in age under 60. A prevalence of occlusion of carotid artery, leading to acute ischemic stroke, was more among male patients. In 59.76% of cases the surgical intervention was carotid endarterectomy. Conclusion: An even more differentiated and personalized approach to the choice of the surgical treatment tactics, taking into account the sex-age aspects and associated diseases, leads to a drastic decrease in the intraoperative risks associated with the surgical interventions and also drastically reduces the incidence of post-operative complications.